Evaluasi Kesehatan Keuangan Melalui Analisis Rasio Keuangan: Studi Kasus PT Semen Indonesia (Persero) Tbk - Assandri, Novita; Kusumandari, Nafia (Fakultas Bisnis Institut Ilmu Sosial dan Bisnis Andi Sapada, 2023)
This study aims to analyze the financial performance of PT Semen Indonesia (Persero) Tbk in the 2021-2022 period. The analytical method used is using the ratio of liquidity, solvency, activity, and profitability. The results showed that the liquidity ratio with the calculation indicators using the Current Ratio, Quick Ratio, and Cash Ratio. The Current Ratio, Quick Ratio, and Cash Ratio show